Ответы и объяснения

Лучший Ответ!
2013-01-06T19:13:44+04:00

x^4+x^3+7x^2-13x-6=0

запишем -13х как  -7х-6х

x^4+x^3-7x^2-7x-6x-6=0

x^3(x+1)-7x(x+1)-6(x+1)=0

(x+1)(x^3-7x-6)=0

x+1=0   x^3-7x-6=0

x=-1       запишем -7х как -х-6х

               x^3-x-6x-6=0

               x(x^2-1)-6(x+1)=0

               x(x+1)(x-1)-6(x+1)=0

               (x+1)(x(x-1)-6)=0

                x+1=0  x(x-1)-6=0

                x₂=-1    x^2-x-6=0

                             D=25

                             x₃=3 x₄=-2

классное задание